2006
DOI: 10.1007/s10552-006-0048-0
|View full text |Cite
|
Sign up to set email alerts
|

Serum transforming growth factor-β1 levels and pancreatic cancer risk: a nested case–control study (Japan)

Abstract: Our prospective data indicate that high serum TGF-beta1 levels may be associated with an increased risk of death from pancreatic cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
1
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 20 publications
1
19
1
1
Order By: Relevance
“…Although both our study and the only other study to examine this association, a Japanese cohort including 85 cases [4], found some evidence of a positive association between serum TGF-β1 and pancreatic cancer, the timing of the associations differed. We did not observe any association during the first 10 years of follow-up, whereas the Japanese study observed an association despite having a maximum of approximately 12 years of follow-up.…”
Section: Discussioncontrasting
confidence: 58%
See 3 more Smart Citations
“…Although both our study and the only other study to examine this association, a Japanese cohort including 85 cases [4], found some evidence of a positive association between serum TGF-β1 and pancreatic cancer, the timing of the associations differed. We did not observe any association during the first 10 years of follow-up, whereas the Japanese study observed an association despite having a maximum of approximately 12 years of follow-up.…”
Section: Discussioncontrasting
confidence: 58%
“…One biomarker, serum transforming growth factor-β1 (TGF-β1) concentration, was associated with increased risk in a small case-control study nested within a Japanese cohort which included 85 cases of pancreatic cancer (OR=2.5, 95% CI 0.9-6.9 for highest vs. lowest quartile, p trend = 0.04) [4]. TGF-β1 is a protein that plays an important role in many biological processes including cell proliferation and immune regulation [5].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Both tumor cells and immune cells, such as regulatory T cells and myeloid-derived suppressor cells (MDSC), contribute to enhanced TGF-b production in patients with cancer. Elevated TGF-b levels in serum and tumors correlate with poor prognosis in patients with tumor (5,6). Thus, TGF-b has generated interest as a target for novel anticancer agents.…”
Section: Introductionmentioning
confidence: 99%